Motivasi Generasi Z dalam Memakai Jasa Pinjaman Online di Kota Bengkulu - Cindy Anela Dewilta; Herlina, Muria; Hila, Syahrio Marta (Peksos: Jurnal Ilmiah Pekerjaan Sosial, 2025)
Online loans, commonly referred to as pinjol in Indonesia, are loans conducted online via websites or mobile applications without requiring collateral. In other words, borrowing through online loan platforms can be done without face-to-face interaction. The phenomenon of online loan usage among young people reflects dynamic changes in their financial behavior, which need to be understood more deeply. This study aims to examine the underlying motivations behind Generation Z's use of online lending services, particularly to understand whether these motivations stem from intrinsic or extrinsic factors. The research employs a qualitative approach with a descriptive method. Informants were selected using the snowball sampling technique, in which initial informants recommended subsequent participants until sufficient data were obtained. This research uses data collection techniques by of means observation, interviews and documentation. This research uses data collection techniques by of means observation, interviews and documentation. The research results show that most informants decisions to use online loans were influenced by external factors, particularly threats or pressing circumtances. This was evident in the need to quickly obtain funds to pay for boarding, tuition, installments, or debts arising from online gambling activities. Meanwhile, only a small proportion of informants were driven by intrinsic motivation in using online loan services.